Penerapan Pendekatan Konstruktivisme Berorientasi Green Chemistry untuk Meningkatkan Keterampilan Berpikir Kritis dan Hasil Belajar Kimia SMA - Astuti, Andari Puji (Prosiding KPSDA, 2015)
Learning chemistry require laboratory work to support good teaching and learning process. SMA Muhammadiyah plus Salatiga is the limited number of laboratory and chemicals are available resulting in chemistry learning process is not managed well. Critical thinking skills are underdeveloped learners and learning outcomes prior to remedial classes is low. Green chemistry approach oriented constructivism is one of the alternatives used in solving chemistry problems learning process in SMA Muhammadiyah Plus Salatiga. This approach uses nature as a learning medium. Conservation efforts in the field of education. This study aims to improve critical thinking skills and student learning outcomes. This study uses a class action research consisting of three cycles .. The results showed a significant difference to the cognitive learning and critical thinking skills in each cycle. Completeness average for cognitive learning outcomes in each cycle reaches 70%, 82% and 88%. Critical thinking skills were observed through the activities of students in the class average for each cycle is 90. More than 75% of students responded positively to the learning chemistry with green chemistry oriented constructivism approach. Learners become actively involved in the learning process and have high initiative in developing the subject in class.